A survey on fecal coliform count and ammonia concentration using tap and filter water samples collected from tea-stalls and roadside restaurants of Mohakhali, Dhaka. - Shahid, Afrida Andaleeb (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.